Nitrogen-rich hollow carbon nanosphere filled Prussian blue analogue composite burning rate catalyst

By filling Prussian blue analogs in nitrogen-rich hollow carbon nanospheres and achieving in-situ growth by ultrasonic method, the problem of metal compounds aggregating large particles on nanocarbon materials is solved, the specific surface area and catalytic effect of the catalyst are improved, and efficient catalysis of thermal decomposition of energy-containing materials is achieved.

CN119504326APending Publication Date: 2025-02-25SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411452866.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In existing solid propellants, metal compounds loaded on nanocarbon materials are prone to aggregate into large particles, making it difficult to control the size of nanoparticles, resulting in a decrease in the specific surface area of ​​the composite material and poor catalytic effect.

Method used

By filling the Prussian blue analog in nitrogen-rich hollow carbon nanospheres, two-step ultrasonic method is used to fill the hollow carbon nanospheres with transition metal nitrate and potassium ferrocyanide respectively to achieve in-situ growth of the Prussian blue analog and enhance the catalytic effect.

Benefits of technology

The specific surface area and catalytic activity of the composite material are improved, and the catalytic effect on the thermal decomposition of energy-containing materials is significantly improved. It is low in cost, easy to prepare and can be produced in large quantities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504326A_ABST
    Figure CN119504326A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-rich hollow carbon nanosphere filled Prussian blue analogue composite burning rate catalyst, which is prepared by the following steps: reacting tetraethyl orthosilicate, resorcinol, melamine, formaldehyde and ammonia water in a mixed solvent of water and ethanol to generate nitrogen-rich carbon spheres, then calcining and etching to form nitrogen-rich hollow carbon nanospheres, and finally preparing the nitrogen-rich hollow carbon nanospheres into the Prussian blue analogue composite burning rate catalyst. And respectively filling transition metal nitrate and potassium ferricyanide by using a two-step ultrasonic method, and generating the Prussian blue analogue in the cavity. The nitrogen-rich hollow carbon nanospheres are filled with the Prussian blue analogues through a two-step ultrasonic method, the Prussian blue analogues are limited to the nanometer size through the confinement effect of the nitrogen-rich hollow carbon nanospheres, and meanwhile the synergistic catalysis effect of the nitrogen-rich hollow carbon nanospheres and the Prussian blue analogues is enhanced; the obtained composite burning rate catalyst has a good catalytic effect on AP.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid propellants, and in particular relates to a nitrogen-rich hollow carbon nanosphere filled with a Prussian blue analogue composite burning rate catalyst. Background Art

[0002] Solid propellants have a wide range of applications in the aerospace and defense fields, such as in rockets, missiles, and missile defense systems. Through combustion, solid propellants can release the chemical energy they contain, which is then converted into kinetic energy by rocket engines. This makes the combustion performance of propellants an important factor in determining the ballistic performance of rocket engines. Solid propellants have a simple structure, are easy to store and handle, and can work normally in extreme environments. According to the composition, solid propellants are mainly divided into double-base propellants and composite propellants. Composite propellants are further divided into modified and unmodified double-base propellants. The main components of composite propellants include oxidizers, high-energy combustion agents, combustion performance regulators, adhesives, stabilizers, and antioxidants, which work together to ensure that the propellant has excellent combustion performance and mechanical properties. Burning rate catalysts play a key role in solid propellants. According to their functions, catalysts can be divided into burning rate catalysts and burning rate inhibitors. In order to improve the burning rate, mechanical strength and environmental adaptability of solid propellants, while reducing the pressure index and enhancing combustion stability, the addition of burning rate catalysts is essential. By scientifically and rationally selecting and proportioning these ingredients, the comprehensive performance of solid propellants can be significantly improved, enabling them to perform well in various applications.

[0003] Hollow carbon nanospheres are a very important type of nanocarbon material. They have been widely used in many fields due to their excellent mechanical stability, high specific surface area, and adjustable physical and chemical properties. The unique spherical structure of hollow carbon nanospheres has attracted much attention in research and application. This spherical structure not only significantly increases the specific surface area, but also effectively disperses and loads metal nanoparticles or other active substances on its surface or inside, thereby enhancing the synergistic catalytic effect between metals and hollow carbon nanospheres. In addition, the pore size and particle size distribution of hollow carbon nanospheres can be adjusted according to different requirements of catalytic effects, and can adapt to the application requirements of various types of catalysts. These characteristics make hollow carbon nanospheres show great potential in the fields of catalysis, energy storage, and environmental protection. In recent years, the filling problem of carbon nanospheres has received a lot of attention and research in the field of catalysis. Zhang et al. efficiently synthesized petal-shaped molybdenum disulfide nanosheets in hollow mesoporous carbon spheres, effectively controlled and restricted the in situ growth of MoS2 nanosheets, and achieved a high reversible capacity (1A g after 200 cycles). -1 The capacity is 993mA hg -1 ), excellent rate capability (10A g -1The capacity at current density is 595mA hg -1 ) and excellent cycle performance (1A g after 1000 cycles -1 The capacity is 962mA hg -1 ) and significantly improved the conductivity and structural stability of composite carbon materials (Zhang X, Zhao R, Wu Q, et al. Petal-like MoS2 nanosheets space-confined in hollow mesoporous carbon spheres for enhanced lithium storage performance[J]. ACS Nano, 2017, 11(8): 8429-8436.).

[0004] Prussian blue analogs are a class of compounds with adjustable composition and open framework that have the structural characteristics of Prussian blue and have a unique hexagonal crystal structure. This unique crystal structure provides a large number of active sites, which can effectively increase the surface area of ​​the catalyst and improve the catalytic efficiency. It is also highly stable and not prone to dissolution and loss, ensuring the durability and reliability of the catalyst during the reaction. This unique structure gives Prussian blue analogs many excellent physical and chemical properties, making them widely used in many fields. Huang Chi et al. explored the synthesis strategy of highly open three-dimensional framework structure Prussian blue analogs (CoFe-PBA) through structural self-transformation guided by template-mediated epitaxial growth, restricted assembly and directed assembly. The results show that confining AP to the framework of CoFe-PBA can achieve unexpected thermal decomposition behavior. The peak temperature of the high-temperature decomposition stage of AP can be advanced to 283.6°C, and the weight loss rate can reach 390.03%min. -1 (ZhouP,Tang

[0005] In summary, in order to improve the various indicators of solid propellant, adding a certain amount of burning rate catalyst is indispensable. After research, nano carbon material has attracted much attention due to its large specific surface area, ultra-high porosity, stable structure and adjustability of pore size, and as an efficient carrier, has good development prospects in the field of combustion catalysis. In addition, Prussian blue analogue is a kind of adjustable framework complex with good stability and more active sites. However, most of the metal compounds loaded on nano carbon material are easily aggregated into large particles on the surface of nano carbon material, and the size of its nano particles is difficult to control, which reduces the specific surface area of ​​the composite material, thereby reducing its catalytic effect on energetic materials. In addition, researchers have found that nitrogen doping of carbon material can also improve the catalytic activity of composite material. Therefore, in order to control the size of metal compound nanoparticles, increase the specific surface area of ​​composite material, and improve the catalytic effect of composite material on thermal decomposition of energetic materials, the present invention fills Prussian blue analogue in nitrogen-rich hollow carbon nanospheres to enhance the catalytic effect of carbon-based composite material on energetic materials. Summary of the invention

[0006] The purpose of the present invention is to provide a nitrogen-rich hollow carbon nanosphere filled with a Prussian blue analogue composite combustion rate catalyst which is simple to prepare, low in cost and can be mass-produced. Transition metal nitrate and potassium ferrocyanide are respectively filled into the interior of the nitrogen-rich hollow carbon nanosphere by a two-step ultrasonic method, and a Prussian blue analogue is in situ grown inside the cavity. The confinement effect and synergistic catalytic effect of the nitrogen-rich hollow nanocarbon sphere and the Prussian blue analogue are utilized to enhance the combustion catalytic effect on the thermal decomposition of AP.

[0007] The nitrogen-rich hollow carbon nanospheres filled with a Prussian blue analog composite burning rate catalyst provided by the present invention is prepared by the following method: adding the nitrogen-rich hollow carbon nanospheres and a dispersant into a transition metal nitrate aqueous solution, filtering and drying after ultrasonic treatment, ultrasonically treating the dried substance in a hexacyanoferrous (ferrous) salt aqueous solution, and then continuing to stir the substance, and then filtering and washing with suction, and vacuum drying to obtain the nitrogen-rich hollow carbon nanospheres filled with a Prussian blue analog composite burning rate catalyst; wherein the hexacyanoferrous (ferrous) salt is any one of potassium ferrocyanide, sodium ferrocyanide, potassium ferrocyanide, and sodium ferrocyanide.

[0008] The above-mentioned transition metal nitrate is any one of Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2.

[0009] Furthermore, it is preferred that the mass ratio of the transition metal nitrate to the hexacyanoferrous salt is 1 to 2:1.

[0010] Furthermore, it is preferred that the mass ratio of the nitrogen-rich hollow carbon nanospheres to the transition metal nitrate is 1:1-20.

[0011] Furthermore, it is preferred that the concentration of the transition metal nitrate in the transition metal nitrate aqueous solution is 0.6 to 5 mg / mL.

[0012] Furthermore, it is preferred that the concentration of the hexacyanoferrous salt in the hexacyanoferrous salt aqueous solution is 0.6 to 5 mg / mL.

[0013] Furthermore, it is preferred that the dispersant is any one of polyvinyl pyrrolidone, polyoxyethylene polyoxypropylene ether, and hexadecyltrimethylammonium bromide.

[0014] Furthermore, it is preferred that the amount of the dispersant added is 20 to 80 times the mass of the nitrogen-rich hollow carbon nanospheres.

[0015] Furthermore, it is preferred that the temperature of the ultrasonic treatment is 20-25°C, the time is 4-10h, and the power is 700-800W.

[0016] Furthermore, it is preferred that the stirring treatment time is 12 to 24 hours.

[0017] Furthermore, it is preferred that the vacuum drying temperature is 60-70° C. and the time is 8-10 h.

[0018] The preparation method of nitrogen-rich hollow carbon nanospheres of the present invention is: tetraethyl orthosilicate, resorcinol, melamine, formaldehyde and ammonia water are stirred in a mixed solvent of water and ethanol to generate nitrogen-rich carbon balls, and then calcined and etched to form nitrogen-rich hollow carbon nanospheres. Among them, the volume ratio of tetraethyl orthosilicate, water, ethanol, ammonia water and formaldehyde is preferably 3-6:15:80:5:0.8-1.5, the mass ratio of resorcinol and melamine is 1:1-2, and the molar ratio of melamine and formaldehyde is 1:2-4; the stirring reaction time is preferably 20-24h, the calcination temperature is 650-750°C, the time is 2-4h, and the calcination atmosphere is nitrogen or argon; the solution used for etching is preferably a 10% HF aqueous solution, and the etching time is 20-24h.

[0019] The beneficial effects of the present invention are as follows:

[0020] 1. The present invention composites nitrogen-rich hollow carbon nanospheres and Prussian blue analogs, utilizes the nanoscale pores of nitrogen-rich hollow carbon nanospheres, and uses a two-step ultrasonic method to fill transition metal nitrate and potassium ferrocyanide into the hollow carbon nanospheres respectively, so that they are confined in the inner cavity of the nitrogen-rich hollow carbon nanospheres, and successfully prepares a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst. In addition, since the particle size of the nitrogen-rich hollow carbon nanospheres is very small, the "confinement effect" of the inner cavity of the nitrogen-rich hollow carbon nanospheres can be used to reduce the prepared Prussian blue analogs to the nanoscale range, thereby increasing the specific surface area of ​​the composite combustion rate catalyst.

[0021] 2. The Prussian blue analogues and nitrogen-rich hollow carbon nanospheres prepared by the present invention have good combustion catalytic performance themselves. The composite material after filling has the conductivity of carbon materials and the stability of Prussian blue analogues, which greatly improves the "synergistic catalytic effect" of hollow carbon nanospheres and Prussian blue analogues, thereby improving the combustion catalytic performance of AP.

[0022] 3. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst of the present invention has low cost, simple preparation method, environmental protection and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the nitrogen-rich hollow carbon nanospheres (NHCs) in Example 1.

[0024] Figure 2 This is a field emission transmission electron micrograph of the nitrogen-rich hollow carbon nanospheres (NHCs) in Example 1.

[0025] Figure 3 This is a field emission transmission electron micrograph of the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analog composite combustion rate catalyst (Co-PBA@NHCs) in Example 1.

[0026] Figure 4 The differential scanning calorimetry curves are respectively added to AP with 5 wt.% of nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst prepared in Examples 1 to 5 and pure AP.

[0027] Figure 5 The differential scanning calorimetry curves of the AP respectively added with 5 wt.% of the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite burning rate catalyst prepared in Examples 1, 6, 7 and 8 and pure AP.

[0028] Figure 6 The differential scanning calorimetry curves are respectively added with 5 wt.% of the nitrogen-rich hollow carbon nanospheres in Example 1, the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analog composite combustion rate catalyst, the combustion rate catalyst of Comparative Example 1 and pure AP. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0030] Example 1

[0031] 4mL tetraethyl orthosilicate, 0.4g resorcinol, 0.4g (3.2mmol) melamine, 1.3mL (9.6mmol) formaldehyde and 5mL ammonia water were reacted in a mixed solvent of 15mL water and 80mL ethanol under magnetic stirring for 24h to generate nitrogen-rich carbon balls. After the reaction, the mixture was washed three times by centrifugation with water and ethanol at a speed of 10000rmp and 5min each time. After the supernatant was completely colorless and transparent, the precipitate was placed in a vacuum drying oven at 60℃ and dried for 8h. The dried sample was then placed in a tube furnace for calcination at a temperature of 700℃, a heating rate of 2℃ / min, a holding time of 3h, and an argon atmosphere. The black powder after calcination was placed in a 10% HF aqueous solution for etching for 24h, filtered and washed with deionized water until neutral, and dried in vacuum at 60℃ to obtain nitrogen-rich hollow carbon nanospheres, which were recorded as NHCs.

[0032] 25 mg NHCs and 2 g PVP were added to 50 mL 3.75 mg / mL Co(NO3)2·6H2O aqueous solution, ultrasonicated at 750 W and 25 °C for 4 h, filtered, and the obtained solid was dried at 80 °C for 6 h. The dried solid was then added to 50 mL 3.75 mg / mL K3[Fe(CN)6] aqueous solution, ultrasonicated at 750 W and 25 °C for 4 h, then stirred at room temperature at 400 rpm for 24 h, filtered, washed with deionized water, and dried in vacuo at 80 °C for 6 h to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite burning rate catalyst, recorded as Co-PBA@NHCs.

[0033] Depend on Figures 1-2 It can be seen that the shape of nitrogen-rich hollow carbon nanospheres is relatively uniform, and the particle size is mainly distributed between 150 and 200 nm. The wall thickness of nitrogen-rich hollow carbon nanospheres is 20 to 25 nm. This structure is a hollow structure with a nitrogen layer formed on the surface. It has a large specific surface area and can effectively disperse and load metal nanoparticles or other active substances on its surface. Figure 3 It can be seen that the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogues composite combustion rate catalysts maintain the structure of the nitrogen-rich hollow carbon nanospheres, and in situ grow cobalt Prussian blue analogues in their cavities, presenting a three-dimensional framework structure of the Prussian blue analogues.

[0034] Example 2

[0035] In this example, the Co(NO3)2·6H2O aqueous solution in Example 1 was replaced by an Fe(NO3)3·9H2O aqueous solution of equal concentration and volume, and the other steps were the same as in Example 1 to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst, which was recorded as Fe-PBA@NHCs.

[0036] Example 3

[0037] In this example, the Co(NO3)2·6H2O aqueous solution in Example 1 was replaced by an aqueous Ni(NO3)2·6H2O aqueous solution of equal concentration and volume, and the other steps were the same as in Example 1 to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst, which was recorded as Ni-PBA@NHCs.

[0038] Example 4

[0039] In this example, the Co(NO3)2·6H2O aqueous solution in Example 1 was replaced by an aqueous Cu(NO3)2·6H2O aqueous solution of equal concentration and volume, and the other steps were the same as in Example 1 to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst, which was recorded as Cu-PBA@NHCs.

[0040] Example 5

[0041] In this example, the Co(NO3)2·6H2O aqueous solution in Example 1 was replaced by an aqueous Zn(NO3)2·6H2O aqueous solution of equal concentration and volume, and the other steps were the same as in Example 1 to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst, which was recorded as Zn-PBA@NHCs.

[0042] Comparative Example 1

[0043] 100 mg Co(NO3)2·6H2O (3.44 mmol) was added to 50 mL deionized water, and stirred at room temperature for 4 h at a speed of 400 rpm. 114 mg K3[Fe(CN)6] (3.46 mmol) was added to the resulting solution, and stirred at room temperature for 24 h under the same conditions. Then, the solution was centrifuged at a speed of 10000 rpm for 5 min for solid-liquid separation, and washed with deionized water for 3 times. The resulting solid was placed in a vacuum drying oven at 60°C and dried for 8 h to obtain brown powder cobalt hexacyanoferrate, recorded as Co-PBA.

[0044] Example 6

[0045] 25 mg NHCs (prepared by the same method as in Example 1) and 2 g PVP were added to 50 mL of 1.25 mg / mL Co(NO3)2·6H2O aqueous solution, ultrasonicated at 750 W and 25° C. for 4 h, filtered, and the obtained solid was dried at 80° C. for 6 h. The dried solid was then added to 50 mL of 1.25 mg / mL K3[Fe(CN)6] aqueous solution, ultrasonicated at 750 W and 25° C. for 4 h, then stirred at room temperature at 400 rpm for 24 h, filtered and washed with deionized water. After the obtained solid was vacuum dried at 80° C. for 6 h, a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst was obtained, recorded as 1.25-Co-PBA@NHCs.

[0046] Example 7

[0047] 25 mg NHCs (prepared by the same method as in Example 1) and 2 g PVP were added to 50 mL of 2.5 mg / mL Co(NO3)2·6H2O aqueous solution, ultrasonicated at 750 W and 25°C for 4 h, filtered, and the obtained solid was dried at 80°C for 6 h. The dried solid was then added to 50 mL of 2.5 mg / mL K3[Fe(CN)6] aqueous solution, ultrasonicated at 750 W and 25°C for 4 h, then stirred at room temperature at 400 rpm for 24 h, filtered and washed with deionized water. After the obtained solid was vacuum dried at 80°C for 6 h, a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst was obtained, recorded as 2.5-Co-PBA@NHCs.

[0048] Example 8

[0049] 25 mg NHCs (prepared by the same method as in Example 1) and 2 g PVP were added to 50 mL of a 5 mg / mL Co(NO3)2·6H2O aqueous solution, ultrasonically treated at a power of 750 W and a temperature of 25°C for 4 h, filtered, and the obtained solid was dried at 80°C for 6 h. The dried solid was then added to 50 mL of a 5 mg / mL K3[Fe(CN)6] aqueous solution, ultrasonically treated at a power of 750 W and a temperature of 25°C for 4 h, and then stirred at room temperature at 400 rpm for 24 h, filtered and washed with deionized water. The obtained solid was vacuum dried at 80°C for 6 h to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst, recorded as 5-Co-PBA@NHCs.

[0050] In order to prove the effective effect of the present invention, 5wt.% nitrogen-rich hollow carbon nanospheres, the burning rate catalyst prepared in Comparative Example 1, and four nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite burning rate catalysts prepared in Examples 1 to 8 were added to AP to test the combustion catalytic performance. The results are shown in Figures 4 to 6 .

[0051] from Figure 4 It can be seen that under the same conditions, when 5 wt.% of the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite burning rate catalyst prepared in Examples 1 to 5 are added to the solid propellant main component AP, the high temperature decomposition peak of AP is advanced from 402.03°C to 289.2°C, 339.4°C, 340.8°C, 314.1°C, and 295.2°C, respectively, which are reduced by 112.83°C, 62.63°C, 61.23°C, 87.93°C, and 106.83°C, respectively, and the heat release of AP is increased from 679.81 J·g -1 Increased to 1733.02 J·g -1 、1712.05J·g -1 、1563.66J·g -1 、1674.87J·g -1 、1519.62J·g -1 , respectively increased by 1053.21 J·g -1 , 1032.24 J·g -1 , 883.85 J·g -1 , 995.06 J·g -1 , 839.81 J·g -1 Among them, Co-PBA@NHCs has the highest heat release for AP thermal decomposition catalysis and the high-temperature decomposition peak for AP thermal decomposition catalysis is the most advanced. From the peak shape, it can be seen that its heat release is also more concentrated.

[0052] from Figure 5 It can be seen that under the same conditions, when 5 wt.% of the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite burning rate catalyst prepared in Examples 1, 6, 7, and 8 are added to the solid propellant main component AP, the high temperature decomposition peak of AP is advanced from 402.03°C to 289.2°C, 303.1°C, 298.3°C, and 291.9°C, respectively, which are reduced by 112.83°C, 99.2°C, 104°C, and 110.4°C, respectively, and the heat release of AP is increased from 679.81 J·g -1 Increased to 1733.02 J·g -1 、1553.94J·g -1 、1663.59J·g -1 、1718.83J·g -1 , respectively increased by 1053.21 J·g -1 , 874.13 J·g -1 , 983.78 J·g -1 , 1039.02 J·g -1The results show that with the increase of Co(NO3)2·6H2O and K3[Fe(CN)6] concentrations, the increase in heat release and the decrease in peak temperature first increase and then decrease, and the relative catalytic activity of the composite combustion rate catalyst of Co-PBA@NHCs for AP is the highest.

[0053] from Figure 6 It can be seen that under the same conditions, when 5wt.% of the composite burning rate catalyst of Example 1 and the nitrogen-rich hollow carbon nanospheres and the burning rate catalyst prepared in Comparative Example 1 are added to the solid propellant main component AP, the high temperature decomposition peak of AP is advanced from 402.03°C to 289.2°C, 383.1°C, and 286.5°C, respectively, which are reduced by 112.83°C, 19.2°C, and 115.8°C, respectively, and the heat release of AP is increased from 679.81J·g -1 Increased to 1733.02 J·g -1 , 1498.43 J·g -1 、1405.17J·g -1 , respectively increased by 1053.21 J·g -1 , 818.62 J·g -1 , 725.36 J·g -1 Compared with the composite combustion rate catalyst of Example 1, the effects of nitrogen-rich hollow carbon nanospheres and comparative example 1 combustion rate catalyst are not as obvious as those of Example 1, which means that the carbon material can only play a synergistic catalytic effect after being compounded with Prussian blue analogs, and the nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogs composite combustion rate catalyst have a better effect.

Claims

1. A nitrogen-rich hollow carbon nanosphere filled with a Prussian blue analogue composite burning rate catalyst, characterized in that: The nitrogen-rich hollow carbon nanospheres and a dispersant are added to an aqueous solution of a transition metal nitrate, and the mixture is filtered and dried after ultrasonic treatment. The dried substance is ultrasonically treated in an aqueous solution of a hexacyanoferrous salt, and then the mixture is continuously stirred, and then filtered, washed, and vacuum dried to obtain a nitrogen-rich hollow carbon nanosphere-filled Prussian blue analog composite combustion rate catalyst; wherein the hexacyanoferrous salt is any one of potassium ferrocyanide, sodium ferrocyanide, potassium ferrocyanide, and sodium ferrocyanide.

2. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analog composite combustion rate catalyst according to claim 1, characterized in that: The transition metal nitrate is any one of Fe(NO3)3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2.

3. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst according to claim 1 or 2, characterized in that: The mass ratio of the transition metal nitrate to hexacyanoferrous salt is 1-2:1; the mass ratio of the nitrogen-rich hollow carbon nanospheres to the transition metal nitrate is 1:1-20.

4. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analog composite combustion rate catalyst according to claim 3, characterized in that: The concentration of the transition metal nitrate in the transition metal nitrate aqueous solution is 0.6-5 mg / mL; the concentration of the hexacyanoferrous salt in the hexacyanoferrous salt aqueous solution is 0.6-5 mg / mL.

5. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst according to claim 1, characterized in that: The dispersant is any one of polyvinyl pyrrolidone, polyoxyethylene polyoxypropylene ether and hexadecyl trimethyl ammonium bromide, and the added amount of the dispersant is 20 to 80 times the mass of the nitrogen-rich hollow carbon nanospheres.

6. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst according to claim 1, characterized in that: The temperature of the ultrasonic treatment is 20-25° C., the time is 4-10 hours, the power is 700-800W, and the time of the stirring treatment is 12-24 hours.

7. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analog composite combustion rate catalyst according to claim 1, characterized in that: The vacuum drying temperature is 60-70° C. and the time is 8-10 hours.

8. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analog composite combustion rate catalyst according to claim 1, characterized in that: The preparation method of the nitrogen-rich hollow carbon nanospheres is as follows: tetraethyl orthosilicate, resorcinol, melamine, formaldehyde and ammonia water are stirred and reacted in a mixed solvent of water and ethanol to generate nitrogen-rich carbon balls, and then calcined and etched to form nitrogen-rich hollow carbon nanospheres; the volume ratio of tetraethyl orthosilicate, water, ethanol, ammonia water and formaldehyde is 3-6:15:80:5:0.8-1.5, the mass ratio of resorcinol and melamine is 1:1-2, and the molar ratio of melamine and formaldehyde is 1:2-4.

9. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst according to claim 8, characterized in that: In the preparation method of the nitrogen-rich hollow carbon nanospheres, the stirring reaction time is 20 to 24 hours, the calcination temperature is 650 to 750° C., the time is 2 to 4 hours, and the calcination atmosphere is nitrogen or argon.

10. The nitrogen-rich hollow carbon nanospheres filled with Prussian blue analogue composite combustion rate catalyst according to claim 8, characterized in that: In the method for preparing nitrogen-rich hollow carbon nanospheres, the solution used for etching is an HF aqueous solution with a mass concentration of 10%, and the etching time is 20 to 24 hours.